Myocardial contractility of the isovolumetrically beating isolated rat heart - De Stefano, L.M. [UNESP]; Matsubara, L.S. [UNESP]; Matsubara, B.B. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2004)
Several indexes of myocardial contractility have been proposed to assess ventricular function in the isovolumetrically beating isolated heart. However, the conclusions reached on the basis of these indexes may be influenced by ventricular geometry rather than contractility itself. The objective of the present study was to assess the performance of widely used contractility indexes in the isovolumetrically beating isolated heart in two experimental models of hypertrophy, the spontaneously hypertensive rat (SHR) and infrarenal aortocava fistula. Compared to normotensive controls (N = 8), SHRs with concentric hypertrophy (N = 10) presented increased maximum rate of ventricular pressure rise (3875 ± 526 vs 2555 ± 359 mmHg/s, P < 0.05) and peak of isovolumetric pressure (187 ± 11 vs 152 ± 11 mmHg, P < 0.05), and decreased developed stress (123 ± 20 vs 152 ± 26 g/cm², P < 0.05) and slope of stress-strain relationship (4.9 ± 0.42 vs 6.6 ± 0.77 g/cm²/%). Compared with controls (N = 11), rats with volume overload-induced eccentric hypertrophy (N = 16) presented increased developed stress (157 ± 38 vs 124 ± 22 g/cm², P < 0.05) and slope of stress-strain relationship (9 ± 2 vs 7 ± 1 g/cm²/%, P < 0.05), and decreased maximum rate of ventricular pressure rise(2746 ± 382 vs 3319 ± 352 mmHg, P < 0.05) and peak of isovolumetric pressure (115 ± 14 vs 165 ± 13 mmHg/s, P < 0.05). The results suggested that indexes of myocardial contractility used in experimental studies may present opposite results in the same heart and may be influenced by ventricular geometry. We concluded that several indexes should be taken into account for proper evaluation of contractile state, in the isovolumetrically beating isolated heart.
Keywords: Myocardial hypertrophy; Ventricular dilation; Pressure overload; Volume overload